CORPORATE SOCIAL RESPONSIBILITY IN EUROPEAN AND ASIAN COUNTRIES - Alas, Ruth .; Lorents, Peeter .; Matsak, Erika .; Übius, Ülle . (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract : The purpose is to study the two facets of corporate social responsibility (CSR) and their similarities and differences between European and Asian countries in different industries. A survey was conducted in Estonian, Chinese, Finnish, Slovakian and Japanese enterprises. Data about two facets of corporate social responsibility, three different branches and five different countries were compared by applying Lorents’s metrics. The ordered pairs were created for each branch and country priorities separately. The distances between priorities were calculated. The total number of respondents was 4187. CSR is influenced by social and cultural environment and industry where the organisation operates. From two facets of CSR the firm respect the interests of agents is more connected with cultural backround than with economic development. The second facet of CSR - firm performance concerning social issue – is more connected with industry than culture. There could also be other factors like ethics, leadership, innovation influencing corporate social responsibility and its similarities and differences in different countries.Keywords :corporate social responsibility, China, Estonia, Finland, Slovakia and Japan